Advanced construction strategies to obtain nanocomposite hydrogels for bone repair and regeneration - Wang Ding; Yuxiang Ge; Tikai Zhang; Cheng Zhang; Xiaofan Yin (NPG Asia Materials)
Abstract Bone tissue engineering is pivotal in facilitating bone reconstruction by promoting persistent angiogenesis and osteogenesis. Initially, the hot gel composite hydrogel scaffold technique was employed. However, to address various limitations, numerous gel structures have since been developed, including osteogenic gellan gels, semi-interpenetrating network hydrogels, photoinduced crosslinking methacrylate gels, and supramolecular hydrogels. This review examines the mechanisms, formation principles, and medical benefits of these gel structures. In addition, novel bioengineering techniques to regulate human bone growth are expected to emerge in the future. This work is expected to significantly expedite the advancement of hydrogel membranes in the field of bone repair.